Recepcja twórczości Olgi Tokarczuk w Bułgarii - Gołek-Sepetliewa, Dorota (Przekłady Literatur Słowiańskich, 2020)
This article discusses Olga Tokarczuk’s presence in Bulgaria, drawing on R. Cudak’s theory of reception while presenting translations, strategies of publication and promotion, literary and critical reflection, and non-literary forms of reception. Widescale, effective, and multi-dimensional promotion, reliable translation (S. Borisova, D. Hamze, H. Simeonova-Mitova, G. Krastev), as well as the openness and interest of readers, have created possibilities for an increase in the popularity of Olga Tokarczuk’s works in Bulgaria within the last two decades. The development in Bulgarian culture of critical and literary thought surrounding Tokarczuk’s works (M. Grigorova) is accompanied by the presence of book translations and other selected texts in leading newspapers and magazines („Literaturen vestnik”, „Panorama”, „Kultura”), constituting a significant platform for the popularization of Polish literature.